Recent observation of anomalous superconducting behavior of ultrathin YBCO films and single crystals of cluster borides - Gasparov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We report the number of deviations from conventional behavior in superconducting properties of ultrathin (1–3 unit-cell (UC)) YBa2Cu3O7–x films sandwiched between semiconducting Pr0.6Y0.4Ba2Cu3O7–x layers and for single crystals of cluster superconductor: dodecaboride ZrB12. We have found a quadratic temperature dependence of the kinetic inductance, Lk-1( T ), at low temperatures independent of frequency, with a break in slope at TBKTdc, the maximum of real part of conductance, ws1(T), and a large shift of the break temperature and the maximum position to higher temperatures with increasing frequency w. We obtain from these data the universal ratio TBKTdc /Lk-1 ( TBKTdc ) = 25, 25, and 17 nHK for 1-, 2- and 3-UC films, respectively in close agreement with theoretical prediction for vortex—antivortex unbinding transition. Superfluid density of ZrB12 displays unconventional temperature dependence with pronounced shoulder at T/Tc equal to 0.65. Contrary to conventional theories we found a linear temperature dependence of Hc2(T) from Tc down to 0.35 K. We suggest that both l(T) and Hc2(T) dependencies can be explained by a two band BCS model with different superconducting gap and Tc.